Wartość aktywów netto otwartego funduszu emerytalnego a stopa zwrotu z jednostki rozrachunkowej - Adamczyk, Piotr; Chmielewski, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of the article was to determinate the existence of relation between the value of net assets of open pension fund and the rate of return from unit of account. To estimate this relation the author used independent two-sample t-test. In the analysed period, at the signifi cance level of ? = 0,05, the empricial value of T statistic was not the basis to reject the null hypothesis. It showed that there was no statistically signifi cant difference between the reasults obtained by the biggest and the smallest pension funds. The examined period related to the years 2001–2010. The author used the data from the Polish Financial Supervision Authority